1999
DOI: 10.1136/thx.54.7.572
|View full text |Cite
|
Sign up to set email alerts
|

Increased exhaled nitric oxide in patients with stable chronic obstructive pulmonary disease

Abstract: Background-Nitric oxide (NO) plays an important role as an inflammatory mediator in the airways. Since chronic obstructive pulmonary disease (COPD) is characterised by airway inflammation, a study was undertaken to determine NO levels in the exhaled air of patients with COPD. Methods-Two groups of patients with clinically stable COPD were studied, 10 current smokers and 10 ex-smokers. Two control groups of healthy subjects consisting of 10 current smokers and 20 nonsmokers were also studied. Exhaled NO levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
85
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 20 publications
10
85
3
3
Order By: Relevance
“…Consistent with prior studies [1][2][3][4][5][6][7][8], it was found that FeNO levels were significantly lower in smokers compared with nonsmokers (geometric mean¡SD): 13.9¡18.0 ppb versus 20.5¡21.3 ppb (p,0.0001); difference56.6 ppb (confidence interval (CI) 4.1-9.2). As shown in figure 2, there was an association of FeNO levels with serum cotinine levels in smokers; serum cotinine levels were inversely correlated with FeNO levels in smokers (r 2 50.13; p50.0003), suggesting that lower FeNO levels were associated with increased levels of tobacco smoke exposure.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with prior studies [1][2][3][4][5][6][7][8], it was found that FeNO levels were significantly lower in smokers compared with nonsmokers (geometric mean¡SD): 13.9¡18.0 ppb versus 20.5¡21.3 ppb (p,0.0001); difference56.6 ppb (confidence interval (CI) 4.1-9.2). As shown in figure 2, there was an association of FeNO levels with serum cotinine levels in smokers; serum cotinine levels were inversely correlated with FeNO levels in smokers (r 2 50.13; p50.0003), suggesting that lower FeNO levels were associated with increased levels of tobacco smoke exposure.…”
Section: Resultssupporting
confidence: 78%
“…However, given the significant association of cigarette smoking with lower FeNO levels [1][2][3][4][5][6][7][8], ATS questionnaire data on smoking [34] were collected and serum cotinine levels were measured [36,37] as a way to rigorously exclude smoking as a potential confounder of FeNO levels. To confirm the validity of using serum cotinine levels as a surrogate marker of cigarette smoking, cotinine levels were compared in subjects who selfreported cigarette smoking on the ATS questionnaire with subjects that did not report smoking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of asthmatic subjects to antigen (Alving et al, 1993) and exacerbations in individuals with COPD (Bhowmik et al, 1998;Corradi et al, 1999) are associated with increases in levels of exhaled nitric oxide (NO). Derived from the nitric oxide synthase (NOS) conversion of L-arginine to L-citrulline, a basal level of the free radical, NO, maintains bronchodilatory airway tone, suppresses leukocyte activation and inhibits microvascular leakage (Barnes et al, 1999;Colasanti & Suzuki, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to persons without COPD, patients with COPD have increased numbers of inflammatory cells in bronchoalveolar lavage and lung biopsy samples [Baraldo et al 2004;Hogg et al 2004;Turato et al 2002], elevated cytokine levels in induced sputum [Vernooy et al 2002;Keatings et al 1996], and elevated fractions of nitric oxide (F E NO) in exhaled breath [Montuschi et al 2001;Corradi et al 1999;Kanazawa et al 1998;Maziak et al 1998]. Many patients with COPD also show evidence of systemic inflammation, as evidenced by elevated serum levels of proinflammatory cytokines and C-reactive protein (CRP) [Mannino et al 2003;Dentener et al 2001;Eid et al 2001;Mendall et al 2000;Takabatake et al 2000;Schols et al 1996].…”
Section: Introductionmentioning
confidence: 99%